Raku as a Low-Fire Finishing Strategy for Galogandang Earthenware: An Experimental Study of Glaze Oxide Variation - Rahmat Hafiz Fauzi (Corak, 2026)
This pilot study investigates raku as a low-fire finishing strategy for Galogandang earthenware (balango) by examining how controlled oxide variation affects raku surface outcomes under a consistent firing and staged reduction protocol. A single low-fire base glaze was prepared and modified using a fixed total coloring-oxide addition of 2 wt%, while the CuO–Fe₂O₃ ratio was varied across five compositions (S1–S5). Test pieces were formed from Galogandang clay, bisque-fired, glaze-applied by spraying, then raku-fired to a peak temperature of 1000°C followed by a 30-minute staged reduction. Surface outcomes were documented photographically and evaluated using ordinal visual indicators for metallic lustre intensity, crackle visibility, glaze stability/continuity, and defect severity (pinholes/bubbles/blistering). Results show a clear trade-off between achieving strong metallic lustre and maintaining surface stability on a porous low-fire body. The copper-dominant composition produced the strongest metallic raku character with minor defects, while increasing iron content generally reduced lustre and increased defect expression, with severe breakdown at higher Fe₂O₃ ratios. The iron-dominant composition yielded a more stable smoked surface with minimal metallic character. These findings support raku as a feasible differentiation strategy for Galogandang/balango, provided oxide composition and process control are balanced to limit defects.